The last one [large type] - Hall, Rachel Howzell (Thorndike Press large print high octane., 2024)
"Thrown into a desolate land of sickness and unnatural beasts, Kai wakes in the woods with no idea who she is or how she got there. All she knows is that if she cannot reach the Sea of Devour, even this hellscape will get worse. But when she sees the village blacksmith fight invaders with unspeakable skill, she decides to accept his offer of help. As she searches for answers, Kai only finds more questions, especially regarding the blacksmith who can ignite her body like a flame, then douse it with ice in the next breath. And no one is what--or who--they appear to be in the kingdom of Vinevridth, including the man whose secrets might be as deadly as the land itself"--